Estimating the environmental impact of a large Tier 2 - Bauer,D; Fayer,S; Whitehouse,D (EDP Sciences, 2024)
Recent years have seen an increasing interest in the environmental impact, especially the carbon footprint, generated by the often large scale computing facilities used by the communities represented at CHEP. As this is a fairly new requirement, this information is not always readily available, especially at universities and similar institutions which do not necessarily see large scale computing provision as their core competency. We present the results of a survey of a large WLCG Tier 2 with respect to power usage and carbon footprint leveraging all sources of information currently available to us. We show that it is possible to estimate the environmental impact with respect to power usage without having to invest in dedicated monitoring equipment. Manufacturers however do not yet provide sufficient information to allow for a detailed analysis of the carbon footprint of equipment manufacture, but even with the available information it is clear that this cannot be ignored.